Potential Gene Therapy: Intravenous Administration of Phagocytes Transfected Ex Vivo with FGF4 DNA/Biodegradable Gelatin Complex Promotes Angiogenesis in Animal Model of Myocardial Ischemia/Reperfusion Injury - Shizuma, Toru; Tanaka, Chiharu; Mori, Hidezo; Fukuyam, Naoto (IntechOpen, 2011)
None